Microbial eukaryotes in the suboxic chemosynthetic ecosystem of Movile Cave, Romania. Issue 3 (26th April 2019) - Reboul, Guillaume; Moreira, David; Bertolino, Paola; Hillebrand‐Voiculescu, Alexandra Maria; López‐García, Purificación
Summary: Movile Cave is a small system of partially inundated galleries in limestone settings close to the Black Sea in Southeast Romania. Isolated from the surface for 6 million years, its sulfidic, methane and ammonia‐rich waters harbour unique chemosynthetic prokaryotic communities that include sulphur and ammonium‐metabolizing chemolithotrophs, methanogens, methanotrophs and methylotrophs. The cave also harbours cave‐dwelling invertebrates and fungi, but the diversity of other microbial eukaryotes remained completely unknown. Here, we apply an 18S rRNA gene‐based metabarcoding approach to study the composition of protist communities in floating microbial mats and plankton from a well‐preserved oxygen‐depleted cave chamber. Our results reveal a wide protist diversity with, as dominant groups, ciliates (Alveolata), Stramenopiles, especially bicosoecids, and jakobids (Excavata). Ciliate sequences dominated both, microbial mats and plankton, followed by either Stramenopiles or excavates. Stramenopiles were more prominent in microbial mats, whereas jakobids dominated the plankton fraction of the oxygen‐depleted water column. Mats cultured in the laboratory were enriched in Cercozoa. Consistent with local low oxygen levels, Movile Cave protists are most likely anaerobic or microaerophilic. Several newly detected OTU clades were very divergent from cultured species or environmental sequences in databases and represent phylogenetic novelty, notably within jakobids. Movile Cave protists likely cover a variety of ecological roles in this ecosystem including predation, parasitism, saprotrophy and possibly diverse prokaryote‐protist syntrophies.